Assessment of Complaint Processes at a Distribution Company Using Logistic Regression - Marcin ŚLĘZAK; Daria WITKOWSKA (Communications of International Proceedings, 2020)
Manufacturers compete and constantly expand their offers, but the technological level and market opportunities mean that the quality and technical differences between the offered products are less and less visible. The result is an increase in intangible assets, in particular proper customer service, which has recently become a necessary condition in building customer satisfaction and loyalty. A satisfied customer will come back to make a purchase again, what's more, he can encourage other people. That is why reverse logistics and related to it after-sales service, which has become the subject of the examination of this article, play such an important role in the operations of enterprises. Based on the empirical data regarding complaint decisions, the impact of selected predictors on the binary dependent variable was assessed, i.e. complaint consideration or rejection. The logistic regression model was used for this purpose. The analysis presented allowed to assess the reliability of complaint processes at the examined company.
Keywords: Complaints; logistic regression; complaint time; complaint cost.